The impact of historical redlining on neurosurgeon distribution and reimbursement in modern neighborhoods - Kabangu, Jean-Luc K.; Dugan, John E.; Joseph, Benson; Hernandez, Amanda; Newsome-Cuby, Takara; Fowler, Danny; Bah, Momodou G.; Fry, Lane; Eden, Sonia V. (Frontiers in Public Health, 2024)
Background: This study examines the lasting impact of historical redlining on contemporary neurosurgical care access, highlighting the need for equitable healthcare in historically marginalized communities.Objective: To investigate how redlining affects neurosurgeon distribution and reimbursement in U.S. neighborhoods, analyzing implications for healthcare access.Methods: An observational study was conducted using data from the Center for Medicare and Medicaid Services (CMS) National File, Home Owner's Loan Corporation (HOLC) neighborhood grades, and demographic data to evaluate neurosurgical representation across 91 U.S. cities, categorized by HOLC Grades (A, B, C, D) and gentrification status.Results: Of the 256 neighborhoods, Grade A, B, C, and D neighborhoods comprised 5.40%, 18.80%, 45.8%, and 30.0% of the sample, respectively. Grade A, B, and C neighborhoods had more White and Asian residents and less Black residents compared to Grade D neighborhoods (P<.001). HOLC Grade A